Statistical analysis of cryptographic strength of SHA-3 competition finalists using nist SP 800-22 methodology - Rzayev, Khazail; Hasanova, Shayasta; Korol, Olha; Aksonova, Iryna; Bukatych, Illia (Національний технічний університет "Харківський політехнічний інститут", 2026)
In today's conditions of rapid development of information technologies and the growth of the number of cyber threats, ensuring the cryptographic stability of hash functions is one of the key tasks of information security. The reliability of hash algorithms directly affects data protection, digital signature, authentication and information integrity. The evaluation of candidates for the competition for the selection of the standard hash algorithm SHA-3, organized by the National Institute of Standards and Technology (NIST), in order to increase the level of cryptographic security after the identification of vulnerabilities in previous algorithms of the SHA family, is of particular relevance.

У сучасних умовах швидкого розвитку інформаційних технологій та зростання кількості кіберзагроз забезпечення криптографічної стійкості хеш-функцій є одним із ключових завдань інформаційної безпеки. Надійність хеш-алгоритмів безпосередньо впливає на захист даних, цифровий підпис, автентифікацію та цілісність інформації. Особливу актуальність має оцінювання кандидатів на конкурс з вибору стандартного хешалгоритму SHA-3, організований Національним інститутом стандартів і технологій (NIST) з метою підвищення рівня криптографічної безпеки після виявлення вразливостей у попередніх алгоритмах сімейства SHA.
Статистичний аналіз криптографічної стійкості фіналістів конкурсу SHA 33 А методологієюnist SP 800-22
Keywords: cryptographic hash function; statistical testing; cryptographi strength; криптографічна хеш-функція; статистичне тестування; криптографічна стійкіст